Effects of ivermectin, phoxim and propetamphos+cypermethrin combination against sarcoptic mange in new zealand rabbits - Bilal Dik; Uğur Uslu (Eurasian Journal of Veterinary Sciences)
This study was carried out on 258 New Zealand rabbits naturally infested with sarcoptic mange. The rabbits divided into four goups. Twenty rabbits in the first Group were treated with Ivermectin (MektiverR) at the dose rate of 200 mcg/bw, subcutaneously. 95 rabbits In Group II and 123 rabbits in Group III were bathed with Phoxim (SebacilR) 0,1 % and Propetamphos+Cypermethrin combination (BloticR) 0,2 %, respectively. The rabbits in these groups were retreated ten days later, secondly. Twenty rabbits in Group IV were used as control. Ten, 20, 30 and 40 days after the first application, all rabbits were inspected macroscopically for sarcoptic mange. In addition skin scru-pings taken the animals were examined for Sarcoptes scabiei under a tight microscope. It was observed that starting to recovery of the rabbits injected ivermectin earlier than in the other groups and lollowed that the rabbits bathed by Phoxim and Propethampos+ Cypermethrin combination, respectively. No found Sarcoptes scabiei in the rabbits in Group I 20 th days from lirst ivermectin injection, However, the mites were not observed in the animals in Group II bathed by Phoxim, 30 days later. In the other hand, the rabbits in Group III bathed by Propetamphos+Cypermethrin combination had Sarcoptes scabiei during the study, but their numbers were decreased gradually. The results showed that, ellicacy of Ivermectin, Phoxim and Propetamphos+Cypermethrin combination was very high, fairly high and less against sarcoptic mange in rabbits, respectively.